Fusion radiology in interventional endoscopy (FRIend): a new approach for pancreatic fluid collections - Sassatelli, Romano; Grillo, Simone; Ottone, Marta; Besutti, Giulia; Cecinato, Paolo; Sereni, Giuliana; Mirante, Vincenzo Giorgio; Iori, Veronica; Pattacini, Pierpaolo; Rossi, Paolo Giorgi (Endoscopy International Open, 2022)
Background and study aims Fusion imaging consists of overlaying preoperative imaging over live fluoroscopy, providing an augmented live guidance. Since 2017, we have been using a new hybrid operating room (Discovery IGS 740 OR, GE Healthcare) for biliopancreatic endoscopy, combining fusion imaging with traditional endoscopic ultrasound (EUS). This study aimed to assess the advantages that fusion imaging could bring to EUS-guided drainage of post-pancreatitis fluid collections.Patients and methods Thirty-five drainage procedures performed between 2012 and 2019 with traditional guidance and fusion imaging were retrospectively compared, assessing the overall treatment success rate – i. e. symptom improvement with complete PFC emptying – as a primary outcome.Secondary outcomes included technical success rate, time to resolution, hospital stay length, adverse events, recurrence rate, and procedure time.Results Patients treated with standard EUS (n = 17) and with fusion imaging (n = 18) were homogeneous in age, gender, pancreatitis etiology, and indication for drainage; the second group had larger PFCs, more frequently walled-off necrosis than pseudocysts, and were treated more emergently, indicating higher case complexity in this group. During the period when fusion imaging was adopted, procedures had a higher overall treatment success rate than during the period when standard EUS was adopted (83.3 % vs. 52.9 %, P = 0.075), and complete emptying was reached in less time (61.1 % vs. 23.6 % complete emptying within 90 days, P = 0.154), differences compatible with random fluctuations.Conclusions This study suggests that fusion imaging in combination with EUS might improve clinical and procedural outcomes of PFC drainage.